Le port antique de Saintes/Mediolanum (Charente-Maritime) - Baigl, Jean-Philippe; Camus, Adrien; Dayrens, Olivier; Lebaron, Vincent; Letuppe, Jonathan; Mathé, Vivien (Gallia, 2020)
Saintes/Mediolanum (Charente-Maritime) possède toutes les caractéristiques urbaines des grandes villes gallo-romaines, avec notamment des monuments remarquables et bien conservés. L’importance de cette agglomération est liée à sa situation sur l’axe routier joignant Lyon, capitale des Trois Gaules, à l’océan Atlantique et croisant ici le fleuve Charente. Cet article synthétique vise à présenter les travaux menés depuis 2014 dans le cadre du projet collectif de recherche « Saintes no limit », dont l’un des axes de recherche concerne les relations de la ville avec le fleuve. Reposant sur une approche diversifiée et collective, cette contribution permet de revenir sur les principales opérations archéologiques récentes, qui ont notamment permis de préciser l’ancien trait de rive antique, d’apporter un nouvel éclairage sur l’emplacement de l’arc routier dit de Germanicus et du pont associé, tout en validant la présence d’aménagements de berge romains en rive droite du fleuve. Enfin, en aval de la ville, les épaves de deux bateaux antiques découvertes en 2008 au fond de la Charente et à hauteur de Courbiac, ont été soumises à de récentes opérations de terrain, permettant ainsi de préciser leur système de construction, de type « romano-celtique ». Saintes/Mediolanum (Charente-Maritime) exhibits all the urban features characteristic of large Gallo-Roman cities, including remarkable and well-preserved monuments. The importance of this agglomeration is linked to its location on the road connecting Lyon/Lugdunum, capital of the Three Gauls, to the Atlantic Ocean and crossing the Charente river here. This short article aims to present the work carried out since 2014 as part of the collective research project “Saintes no limit”, one research line of which focused the city’s relationship with the river. Based on a diversified and collective approach, this contribution provides an overview of the main archaeological operations carried out recently which yielded information about the existence of potential ancient port infrastructures and activities. Thus, in 2004, a survey evaluation carried out in “place Bassompierre” made it possible to locate the ancient line of the riverbank and shed new light on the location of the so-called Germanicus road arch and the associated bridge. More recently, underwater and geophysical surveys carried out in 2013 and 2014, as well as an initial underwater survey evaluation carried out in the Charente river in 2015, led to the discovery of numerous wooden remains (piles, planks, etc.), suggesting the presence of various Roman riverbank structures, as well as the discovery of a stone structure approximately 3 m thick and over 100 m long, on the right bank of the river. Despite recent major dredging and recalibration work, these various operations have demonstrated the full archaeological potential of the river, suggesting that the embankments of the right side of the Charente river may have been developed over a large part of the area covered by the Roman city. Lastly, downstream from the city of Saintes, the wrecks of two ancient boats discovered in 2008 at the bottom of the Charente and near Courbiac, in the communes of Saintes and Fontcouverte respectively, have been the subject of recent field operations, thus enabling their construction system, of the “Romano-Celtic” type, to be clarified. In conclusion, the collective work undertaken in this place makes it possible to identify a town which is not located on the coast but is connected to the sea via its river. Boats could sail up the river with the help of the tide to Saintes/Mediolanum, where in Roman times the first bridge from the river mouth was located. It is therefore not astonishing that the city capital of the Santones, and perhaps the first capital of Roman Aquitania, was equipped very early on with port facilities, necessary for this loading/unloading area and for its economic development.